THE LARGE SCALE SOCIAL RESTRICTIONS POLICY FOR HANDLING THE COVID-19 PANDEMIC - Fradhana Putra Disantara (UNISSULA, 2020)
This legal research uses a conceptual approach and a statutory approach. This research was carried out by inventorying primary and secondary materials, so as to obtain an appropriate analysis and critical review of published legal issues. The purpose of the study was to analyze the dynamics of Large Scale Social Restrictions Policies, especially regarding the Regulation of Minister of Health Number 9 of 2020and analyze various problematic PSBB policies during the pandemic. This study states that the PSBB is different from regional quarantine. On the other hand, the PSBB regulation in the Regulation of Minister of Health Number 9 of 2020 also raises doubts.Then,the Chief of Police's Declaration Mak/2/III/2020 provided strong legitimacy to strengthen the PSBB policy in terms of public compliance.The PSBB policy by the Central and Regional Governments has left various problems. Starting from material errors, contradiction of the article in the Governor's Regulation, and the Governor's Regulation which is not based on the Law above. The solution that can be done is to revise the Government Regulation No. 21 of 2020 and conduct executive review of the Governor's Regulation.